Sistem Navigasi untuk Individu Pejalan Kaki Berbasis Prinsip Dead Reckoning - Setiawan, Iwan; Setiyono, Budi; Kawuri, Laras Dwi (Transmisi, 2012)
Â This paper discusses a pedestrian navigation system based on the principle of dead reckoning. Early prototype of the system has been developed using only two internal sensors of MEMS accelerometer and electronic compass that is worn over the shoes of the individual. Functionally, accelerometer in this system is used to detect the two state individual legs as walking: stance and swing state, while the electronic compass are functionally used to estimate the direction of individual pedestrian step. Based on initial testing, the navigation system that developed capable of detecting individual steps that are normal walking with 100% success rate, whereas the electronic compass readout accuracy is still room for improvement.Â Keyword : Navigation, Positioning, Dead Reckoning, Pedestrian, Accelerometer, Electronic Compass